In Vitro Selection, Regeneration and Herbicide Tolerant Callus and Suspensions Cell Culture of Rice (Oryza Sativa L.) - Kow, Cheong Wei (1998)
The in vitro establishment of a rapidly growing, embryogenic and friable callus and suspension cell lines of 27 local indica rice (Oryza sativa) cultivars were studied. The regeneration capacity of selected cultivars also observed. Differences in culture conditions, growth rate and plant hormone applications were examined to determine the optimal responses. Rice callus was induced from immature seeds on basal MS solid medium supplemented with 10 µM 2,4-D and finely dispersed cell suspension cultures were initiated from the callus using B5 basal liquid medium consisted of 10 µM 2,4-D. These callus and suspensions were maintained in similar medium, respectively. Basal MS solid medium supplemented with 25 µM BA and 5 µM lAA was most effective for obtaining regenerated plantlets from callus. For cell suspension, regeneration was obtained by using basal MS solid medium with 25 µM BA and 2.5 µM NAA. Out of 27 cultivars investigated, callus of 16 cultivars and cell suspensions of 11 cultivars were suscessfully regenerated. Cultivar Puteh Perak exhibited good response throughout the experiments. Radioactivity study was carried out as a confirmation of2,4-D taken up by the callus and suspension cells. During the stressing and selecting stages, 2,4-D was observed to be taken up by the rice callus and suspension cells. In the selection and toxicity studies, 2,4-D-tolerant callus cultivar Puteh Perak was selected in MS solid media at 400, 600 and 800 µM 2,4-D concentration while tolerant cell-suspension in basal B5 liquid media containing 200 and 400 µM 2,4-D. Both instantaneous and gradual stressing method were carried out. The tolerant callus and cell-suspension were isolated and maintained.